Targeting the Tumor Microenvironment in Renal Cell Cancer Biology and Therapy - Heidegger, Isabel; Pircher, Andreas; Pichler, Renate (Frontiers in Oncology, 2019)
Renal cell cancer (RCC) is a highly vascularized and immunogenic tumor type. Inhibition of vessel formation by anti-angiogenic therapies as well as stimulation of the immune system by immunotherapy have revolutionized the therapeutic landscape of RCC in recent years. Nevertheless, both therapies are associated with therapy resistance due to a highly dynamic, adaptive and heterogeneous tumor microenvironment (TME). The aim of this short review article is to provide an overview of the components of the RCC TME as well as to discuss their contribution to disease progression. In addition, we report preclinical and clinical findings and how the different TME components can be modulated to impede treatment progression as well as to overcome therapy resistance to anti-angiogenic or immunomodulating therapy concepts. Furthermore, we discuss the predictive and prognostic role of the TME in RCC therapy. We also report the concept of combinational targeting of anti-angiogenic therapies and immune checkpoint inhibitor therapy including also latest results of clinical studies discussed at recent oncological meetings. Finally, promising new therapeutic targets within the TME are mentioned.